Frequency and Risk Factors of Anxiety and Depression among Pregnant Women in Abbottabad, Pakistan: A Facility-Based Cross-Sectional Study - Saadia Irum, Adeel Ahmed Khan, Unaib Rabbani, Fahad Saqib Lodhi, Aymen Elsous (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: We determined the frequency and risk factors of anxiety and depression in pregnant patients at an Abbottabad tertiary care hospital district of Khyber Pakhtunkhwa, Pakistan. Methods: Using the validated Urdu version of the Hospital Anxiety and Depression Scale, we conducted a cross-sectional study among 200 pregnant women from April to August 2019 at Ayub Teaching Hospital, a tertiary care hospital (HADS). Unadjusted and adjusted odds ratios for independent factors related with anxiety and depression were calculated using univariate and multivariable logistic regression. Results: Around 70% of the pregnant women were classified as anxious, while 57.5% were depressed. About half of the pregnant women had both depression and anxiety. Multivariate regression analysis showed that combined pregnant women were more likely to experience anxiety and despair belonging to Urdu ethnicity, having low level of education, household income of greater than 30 thousand PKR, husband’s higher level of managerial and professional position, and in 3rd trimester of pregnancy. Conclusion: Depression and anxiety are prevalent throughout pregnancy, according to our research. We suggest that interventions should be designed and implemented through mental health integration at all level of health care by taking into account the associated risk factors can lessen prenatal depression and anxiety among expecting mothers. Keywords: Anxiety, depression, risk factors, pregnant women, Pakistan.